The Quest for Price Stability in Central America and the Dominican Republic* - Parrado, Eric (IMF Working Papers; Working Paper ;, 2007)
This paper addresses the question of why inflation has not yet converged to price stability in Central America and the Dominican Republic and is currently relatively high by Latin American standards. It suggests that despite the institutional strengthening of monetary policy, important flaws remain in most central banks, in particular a lack of a clear policy mandate and little political autonomy, which are adversely affecting the consistency of policy implementation. Empirical analysis reveals that all central banks raise interest rates to curtail inflation but only some of them increase it sufficiently to effectively tackle inflation pressures. It also shows that some central banks care simultaneously about exchange rate stability. The potential policy conflict arising from a dual central bank mandate and the unpredictable policy response is probably undermining markets' confidence in central banks' commitment to price stability, thereby perpetuating an inflation bias.